2006
DOI: 10.1590/s0036-46652006000600003
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of soil contamination by Toxocara canis eggs in the south region of São Paulo municipality (SP, Brazil) in a 18 month period

Abstract: SUMMARYSoil contamination by embryonic eggs of Toxocara canis is the main source of human infection by this ascarid larvae resulting, sometimes, in the occurrence of visceral larva migrans syndrome. The objective of the present research is to determine the frequency of T. canis eggs in soil samples monthly collected in nine public places, located at the South Region of São Paulo municipality in a 18-month period, from February 2004 to July 2005. The soil samples collected were treated with a 30% antiformine so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0
11

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 13 publications
2
9
0
11
Order By: Relevance
“…*Some subjects had more than one sign/symptom; **p < 0.05 = significant value (Chi-square); *** variables in the model: sex, age, pulmonary and hepatic manifestations, headache, and weakness and/or fatigue. In agreement with other authors, we have also found statistically significant differences between gender and positive serology indicating that male subjects are more associated at risk of toxocariasis than female subjects, probably because of their close contact with soil, as is the case with this population, who are farmers 4,5,21,22,26 .…”
Section: Discussionsupporting
confidence: 93%
“…*Some subjects had more than one sign/symptom; **p < 0.05 = significant value (Chi-square); *** variables in the model: sex, age, pulmonary and hepatic manifestations, headache, and weakness and/or fatigue. In agreement with other authors, we have also found statistically significant differences between gender and positive serology indicating that male subjects are more associated at risk of toxocariasis than female subjects, probably because of their close contact with soil, as is the case with this population, who are farmers 4,5,21,22,26 .…”
Section: Discussionsupporting
confidence: 93%
“…This can also attribute to the low prevalence rate observed in this study when compared to the prevalence rate reported twenty seven years back by Gunaseelan et al (1985). The reduction of Toxocara ova over a period of time was also reported from Poznani, Poland (Mizgajska 1997;Masnik 2000), Ankara, Turkey (Oge and Oge 2000;Avcioglu and Burgu 2008), London, UK (Snow et al 1987;Gillespie et al 1991), Salamanca, Spain (Simon and Conde 1987;Conde et al 1989) and Saopolo, Brazil (Santarem et al 1998;Queiroz et al 2006).…”
Section: Discussionmentioning
confidence: 59%
“…The use of public places by people is other important risk factor associated to human toxocariasis, since canine feces are very frequent in public places and playgrounds in other countries 11,25,29,33 . Although limited studies about soil contamination with Toxocara eggs in Peru have revealed a frequency ranging from 30% to 80% 6,21 this risk factor was significantly associated to Toxocara infection.…”
Section: Discussionmentioning
confidence: 99%